THE EFFECT OF DHIKR THERAPY ON ANXIETY IN PREOPERATIVE PATIENTS AT SURGICAL ROOM IN PEMANGKAT GENERAL HOSPITAL IN 2020 - Octary, Tiara; Akhmad, Arif Nur; S, Susito (Tanjungpura Journal of Nursing Practice and Education, 2020)
Perioperative is a surgical process that begins pre surgery (surgery), surgery (intraoperative),  and postoperative (postoperative). While undergoing a preoperative course the patient will  experience anxiety. One way to reduce anxiety levels by giving the dhikr therapy has a relaxing effect.  The purpose of this study was to determine the effect of dhikr therapy on the level of anxiety inpreoperative patients in the surgical ward of the general regional Pemangkat hospital in 2019.  This research used quantitative research with the pre experiment method, and pre and post test  without control group approach. The method of selecting samples in this study uses Non Probability  Sampling with Conseutive Sampling techniques. The sampling technique using one questionnaire,  namely the APAIS (Amsterdam Preoperative Anxiety and Information Scale) questionnaire,  which was conducted 2 times, namely 1 pre and 1 post. The number of samples in this study  were 33 respondents from preoperative patients. The data analysis in this study used Paired T test.The results of the study with the effect of dhikr therapy on the anxiety level of preoperative  patients were produce a P value of 0.00 with a significance value of 0.05. So the value of P 0.05  which means that Ha accepted.  The conclusion of this study found that the Dhikr therapy have positive effect to reduce the levelof anxiety in preoperative patients in the surgical ward of the general regional Pemangkat hospital  in 2019.  For the nursing profession, to the hospital for the respondent institutions, for further research.  Hopefully this research has been done can be put to good use for the delivery of health services in the  future.